Interactions of PLGA nanoparticles with blood components: protein adsorption, coagulation, activation of the complement system and hemolysis studies. Issue 14 (13th March 2015) - Fornaguera, Cristina; Calderó, Gabriela; Mitjans, Montserrat; Vinardell, Maria Pilar; Solans, Conxita; Vauthier, Christine
Abstract : Schematic representation of PLGA nanoparticle interactions with blood components when they enter the bloodstream. Abstract : The intravenous administration of poly(lactic- co -glycolic) acid (PLGA) nanoparticles has been widely reported as a promising alternative for delivery of drugs to specific cells. However, studies on their interaction with diverse blood components using different techniques are still lacking. Therefore, in the present work, the interaction of PLGA nanoparticles with blood components was described using different complementary techniques. The influence of different encapsulated compounds/functionalizing agents on these interactions was also reported. It is worth noting that all these techniques can be simply performed, without the need for highly sophisticated apparatus or skills. Moreover, their transference to industries and application of quality control could be easily performed. Serum albumin was adsorbed onto all types of tested nanoparticles. The saturation concentration was dependent on the nanoparticle size. In contrast, fibrinogen aggregation was dependent on nanoparticle surface charge. The complement activation was also influenced by the nanoparticle functionalization; the presence of a functionalizing agent increased complement activation, while the addition of an encapsulated compound only caused a slight increase. None of the nanoparticles influenced the coagulation cascade at low concentrations. However, at high concentrations, cationized nanoparticles did activate the coagulation cascade. Interactions of nanoparticles with erythrocytes did not reveal any hemolysis. Interactions of PLGA nanoparticles with blood proteins depended both on the nanoparticle properties and the protein studied. Independent of their loading/surface functionalization, PLGA nanoparticles did not influence the coagulation cascade and did not induce hemolysis of erythrocytes; they could be defined as safe concerning induction of embolization and cell lysis.